2021
DOI: 10.3390/ijms22189766
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxygenkwanin Increases the Sensitivity of Liver Cancer Cells to Chemotherapy by Inhibiting DNA Damage Response in Mouse Xenograft Models

Abstract: Molecules involved in DNA damage response (DDR) are often overexpressed in cancer cells, resulting in poor responses to chemotherapy and radiotherapy. Although treatment efficacy can be improved with the concomitant use of DNA repair inhibitors, the accompanying side effects can compromise the quality of life of patients. Therefore, in this study, we identified a natural compound that could inhibit DDR, using the single-strand annealing yeast-cell analysis system, and explored its mechanisms of action and pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“… 47 Hydroxygenkwanin ( HGK ) increases the sensitivity of hepatocellular carcinoma to doxorubicin by downregulating RAD51 . 55 Interferon-regulatory factor-1 can bind to the promoter of RAD51 to inhibit its expression in gastric cancer cells to reverse chemoresistance. 56 (3) In terms of chemotherapy combination with immunotherapy, it has been shown that TNBC with HRD has higher levels of lymphocytic infiltration and that immune checkpoint blockade therapy is an option for this subtype despite the presence of chemoresistance (a more specific analysis of immune infiltration is presented later).…”
Section: Discussionmentioning
confidence: 99%
“… 47 Hydroxygenkwanin ( HGK ) increases the sensitivity of hepatocellular carcinoma to doxorubicin by downregulating RAD51 . 55 Interferon-regulatory factor-1 can bind to the promoter of RAD51 to inhibit its expression in gastric cancer cells to reverse chemoresistance. 56 (3) In terms of chemotherapy combination with immunotherapy, it has been shown that TNBC with HRD has higher levels of lymphocytic infiltration and that immune checkpoint blockade therapy is an option for this subtype despite the presence of chemoresistance (a more specific analysis of immune infiltration is presented later).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hydroxygenkwanin was shown to suppress the cell growth and invasion of hepatocellular carcinoma cells (HCC) by inducing the expression of the microRNA, miR-320a [ 42 ]. Recently, hydroxygenkwanin was found to enhance the chemosensitivity of HCC cells by inhibiting the expression of class I histone deacetylase (HDAC) [ 40 ] and by inhibiting the DNA damage response [ 39 ]. In this study, we investigated the modulatory effect of hydroxygenkwanin on ABCB1- and ABCG2-mediated MDR in multidrug-resistant cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that hydroxygenkwanin is a more potent inhibitor of ABCG2, compared with ABCB1, and is more specific to ABCG2. It is worth noting that in previous studies, high concentrations of hydroxygenkwanin (20–50 μM) were used in biochemical assays [ 39 , 40 , 41 , 42 ]. In contrast, at the highest tested concentration of 1 μM, hydroxygenkwanin reversed ABCG2-mediated MDR in a manner similar to the reference inhibitor, Ko143 ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last study, Chen et al [5] hypothesized that hydroxygenkwanin (HGK) has an inhibitory effect on DNA damage response (DDR)-induced damage and tested it in yeast cells. In addition, the author used liver cancer cells to detect related indicators such as apoptosis and homologous recombination repair and developed a mouse model to confirm the results of in vitro experiments.…”
mentioning
confidence: 99%